The Exercise After Postpartum and Its Benefits for Maternal Mental Health : A Narrative Review - Arista, Devi Maya; Nurvitriana, Nidya Comdeca; Adzra, Sandiena; Nadya Rahmadilla Brahmady; Nabila Natasya Putra; Wijayanti, Karunia (International Conference on Biomedical and Sports Medicine, 2025)
The postpartum period is a critical phase marked by significant physical and psychological adjustments in mothers, including an increased risk of anxiety and depression. Addressing maternal mental health during this period is essential to ensure maternal well-being and the quality of infant care. This study aims to review the benefits of postpartum physical activity on maternal mental health. A narrative review was conducted using databases such as PubMed, Google Scholar, ScienceDirect, and ResearchGate, focusing on publications from 2020 to 2025. The findings consistently indicate that postpartum exercise, including structured routines such as yoga and postpartum exercise, contributes to reduced levels of anxiety and depression while also promoting emotional balance, neurochemical regulation, and psychosocial adjustment. Therefore, physical activity after childbirth can be considered a safe, effective, and accessible strategy to support maternal mental health.